Crystal structure and Hirshfeld surface analysis of 1-[(E)-2-(5-chloro-2-hydroxyphenyl)hydrazin-1-ylidene]naphthalen-2(1H)-one - Hassiba Bougueria; Souheyla Chetioui; Mohammed Abdellatif Bensegueni; Jean-Pierre Djukic; Nesrine Benarous (Acta Crystallographica Section E: Crystallographic Communications, 2021)
The title compound, C16H11ClN2O2, was obtained by diazotization of 2-amino-4-chlorophenol followed by a coupling reaction with β-naphthol. There are two molecules (A and B) in the asymmetric unit. The crystal structure features only one type of intermolecular interaction, that is strong hydrogen bonds involving the hydroxyl group. The naphthol and phenol fragments attached to the C=N—N— moiety exhibit an s-trans conformation. In addition, those fragments are almost coplanar, subtending a dihedral angle of 13.11 (2)° in molecule A and 10.35 (2)° in molecule B. A Hirshfeld surface analysis indicates that the most important contributions to the crystal packing are from H...H (32.1%), C...H/H...C (23.1%), Cl...H/H...Cl (15.2%), O...H/H...O (12.8%) and C...C (9%) contacts.